2013
DOI: 10.1002/ajmg.a.36024
|View full text |Cite
|
Sign up to set email alerts
|

Osteogenesis imperfecta type V: Clinical and radiographic manifestations in mutation confirmed patients

Abstract: Osteogenesis imperfecta (OI) type V is a specific OI phenotype with interosseous membrane calcification of the forearm and hyperplastic callus formation as typical features. The causative gene mutation for OI type V has been recently discovered. The purpose of this report is to review the clinical and radiographic characteristics of mutation confirmed OI type V in detail. Sixteen (nine familial and seven sporadic) patients were enrolled in the study. Blue sclera and dentinogenesis imperfecta were not evident i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
23
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 20 publications
3
23
0
1
Order By: Relevance
“…A wide variability in the age of the first fracture, as well as the total number of fractures, was seen in the patients in the current study. This is consistent with previous reports that included patients with the same mutation, which find that the number of fractures is indeed highly variable; frequencies from 0 to 30 fractures have been reported [Cho et al, 2013;Kim et al, 2013;Lazarus et al, 2014;Reich et al, 2015]. Zhang et al [2013] described 4 Chinese families with individuals aged between 4 and 29 years with the occurrence of 3-11 fractures.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…A wide variability in the age of the first fracture, as well as the total number of fractures, was seen in the patients in the current study. This is consistent with previous reports that included patients with the same mutation, which find that the number of fractures is indeed highly variable; frequencies from 0 to 30 fractures have been reported [Cho et al, 2013;Kim et al, 2013;Lazarus et al, 2014;Reich et al, 2015]. Zhang et al [2013] described 4 Chinese families with individuals aged between 4 and 29 years with the occurrence of 3-11 fractures.…”
Section: Discussionsupporting
confidence: 92%
“…Two previous studies have described the occurrence of vertebral fractures in 87 and 100% of the cases [Lee et al, 2006;Shapiro et al, 2013], and scoliosis was observed at a frequency between 50 and 76% in 5 studies involving 98 individuals [Glorieux et al, 2000;Zeitlin et al, 2006;Kim et al, 2013;Rauch et al, 2013]. Also relevant, the investigators in all these cases observed the patients to exhibit a pyramidal shape of the chest and ribs with an unusual form and downward slanting [Kim et al, 2013]. The cause for this alteration of the rib position and shape is unknown, and this feature has not been described in other types of OI.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations